Effect of the addition of two superoxide dismutase analogues (Tempo and Tempol) to alpaca semen extender for cryopreservation - Santiani Acosta A. (2013)
This research was supported by the National Science and Technology Council (CONCYTEC) of Peru, Research Superior Council of San Marcos University (CSI-UNMSM), and Center of Biotechnology in Reproduction (CEBIOR) of La Frontera University. The authors thank Juan Olazábal and other professionals and students of IVITA-Maranganí for assistance during collection of alpaca semen samples.